Dual harm among patients attending a mental health unit in Uganda: a hospital based retrospective study - Favina, Alain; Abaatyo, Joan; Kaggwa, Mark Mohan (BMC Psychiatry, 2024)
Background: Dual harm encompasses the complex interplay of the co-occurrence of self-harm and aggression. Individuals with dual harm may display a more hazardous pattern of harmful behaviors like homicide-suicide compared to people with sole harm. This study aimed to examine the presence of dual harm among general psychiatry inpatients in a mental health unit in Uganda. Methods: A retrospective chart review of 3098 inpatients from January 2018 to December 2021. Dual harm reported experience at admission was based on experiences of self-harm with harm to people or property or both. Logistic regression assessed the association between dual harm and socio-demographics and clinical characteristics. Results: A total of 29 (1%) patients experienced dual harm, with five having experienced self-harm with both harm to others and property, 23 with harm to people, and one with harm to property. Dual harm was statistically significantly associated with the male gender at bivariate analysis. However, there were no statistically significant factors associated with dual harm at multivariate analysis or sensitivity analysis with the specific types of dual harm. Conclusion: General psychiatry inpatients in Uganda experience dual harm before admission at lower prevalence than in previous literature. However, no investigated sociodemographic and clinical factors could explain these experiences. Further studies looking at dual harm are warranted to understand these unfortunate experiences with serious consequences among patients in Uganda.
Keywords: Dual harm; Self-harm; Aggression; Male; Mental health; Uganda